A definição de actio romana e maximum ético em Joaquim Carlos Salgado - Levindo Ramos Vieira Neto (2017)
The research, based on the Theory of Law and the Philosophy of Law, aims fundamentally to explain the contribution of the institutes of the Roman actio and ethical maximum in the Theory of Justice developed by JOAQUIM CARLOS SALGADO, from the examination of the historical-dogmatic evolution of the concept of actio and its approach in the course of juridical consciousness, and its unfolding in the moment of application of formal and material justice, as manifested in the idea of contemporary justice. The theme makes it possible to revisit several concepts of Law Science, from a juridical-philosophical perspective, and to deepen the studies and contributions of the Theory of Maximum Ethics for the Science of Law, thus demonstrating the unfolding of the Roman legal culture in juridical thought with the purpose of contributing to the best operation of related legal concepts in the contemporary world. To the research, in face of two refined philosophical thoughts, it is the task of presenting the importance of actio to the historical process of justice, in the attempt to recover the roots of law for the discussion of the philosophy of law, that is, to recover the importance of science of Law as an object of the Philosophy of Law. As HEGEL wanted, which had in the particular sciences the object of Science. In this way, the research intends to contribute to a rapprochement of the Philosophy of the Law to its object and to the challenges that Law Science faces in a modern way, whose philosophical reflections must shed light on reflecting on the fundamentals of the Law to rethink its scientific bases.